Приватнопідприємницькі товариства Харкова: виникнення та діяльність в роки НЕПу - Волосник, Ю. П.; Онацький, М. Ю. (НТУ "ХПІ", 2015)
У статті аналізуються виникнення та діяльність підприємницьких товариств у Харкові в роки непу. Проаналізовано правову базу приватних товариств та роль держави в регулюванні діяльності товариств різних типів. Досліджено персональний склад фундаторів товариств повних, на вірі, з обмеженою відповідальністю та акціонерних, роль товариств у економічному житті Харкова, а також процес їх ліквідації в період згортання непу.

The article analyzes the emergence and activities of business entities in Kharkiv in the NEP. Analyzed the legal framework of private societies and the role of the state in regulating the activities of companies of different types. Investigated the composition of the founders of the companies full, faith, limited liability and joint stock, the role of societies in the economic life of Kharkov, and the process of their elimination during the collapse of the NEP. As a result of this situation - different types of private companies during the NEP did not manage to achieve their great potential and become one of the important factors of socio - economic development of Kharkiv.
Public-private partnerships Kharkov: occurrence and activity in the years of the NEP
Keywords: НЕП; Нова економічна політика; приватні підприємства повні; підприємства з обмеженою відповідальністю; підприємства акціонерні; Харків історія; new economic policy; private enterprise; limited liability company; joint stock